2016
DOI: 10.1167/iovs.16-20007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nonperfused Retinal Vessels in Ischemic Retinopathy

Abstract: PURPOSE. Retinal ischemia has been traditionally assessed by fluorescein angiography, visualizing perfused vessels. However, this method does not provide any information about nonperfused vessels, and although it is often assumed that vessels in ischemic areas regress, we know little about how nonperfused retinal vessels change over time. Here, we aim to learn more about the long-term fate of nonperfused vessels in the retinal vasculature.METHODS. Optical coherence tomography (OCT) was used to visualize perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Optical coherence tomography angiography (OCT angiography) was first reported by Makita et al using Doppler OCT [ 1 ]. OCT angiography is a novel technology allowing layer-specific visualization of normal chorioretinal vasculature and neovascularizations without the need for intravenously injected fluorescent dyes [ 2 5 ]. The visualization of normal vessels and pathological neovascularization using OCT angiography has been evaluated in different retinal or choroidal neovascular diseases such as chronic central serous chorioretinopathy, age-related macular degeneration, retinal vein occlusion, diabetic retinopathy, and retinal arterial macroaneurysms and also in different animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Optical coherence tomography angiography (OCT angiography) was first reported by Makita et al using Doppler OCT [ 1 ]. OCT angiography is a novel technology allowing layer-specific visualization of normal chorioretinal vasculature and neovascularizations without the need for intravenously injected fluorescent dyes [ 2 5 ]. The visualization of normal vessels and pathological neovascularization using OCT angiography has been evaluated in different retinal or choroidal neovascular diseases such as chronic central serous chorioretinopathy, age-related macular degeneration, retinal vein occlusion, diabetic retinopathy, and retinal arterial macroaneurysms and also in different animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the reduction of intraocular VEGF concentration following PC should hypothetically improve leukostasis and vascular endothelial cell hypertrophy and ultimately correct the reversible vascular occlusion. However, Powner et al 35 in their study suggested that an en face OCT signal originates from the vessel wall with progressive loss of vascular cells (endothelial cells and pericytes) over time. The remaining acellular basement membrane tubes (ghost vessels) were preserved for many years.…”
Section: Discussionmentioning
confidence: 93%
“…Like our study, Powner et al found retinal vessels on en face OCT without perfusion on OCTA in three patients with BRVO. 3 They speculated that these vessels on en face OCT were acellular basement membrane tubes and went on to support this hypothesis with histologic evidence from a patient with a chronic CRVO. However, our study suggests that at least a subset of these vessels maintain some perfusion given the observed areas of preserved retina.…”
Section: Discussionmentioning
confidence: 99%